Arg-Phe-amide-related peptides influence gonadotropin-releasing hormone neurons - Kelestimur, Haluk; Kacar, Emine; Uzun, Aysegul; Ozcan, Mete; Kutlu, Selim (Editorial Board of Neural Regeneration Research, 2013)
The hypothalamic Arg-Phe-amide-related peptides, gonadotropin-inhibitory hormone and orthologous mammalian peptides of Arg-Phe-amide, may be important regulators of the hypothalamus-pituitary-gonadal reproductive axis. These peptides may modulate the effects of kisspeptins because they are presently recognized as the most potent activators of the hypothalamus-pituitary-gonadal axis. However, their effects on gonadotropin-releasing hormone neurons have not been investigated. In the current study, the GT1-7 cell line-expressing gonadotropin-releasing hormone was used as a model to explore the effects of Arg-Phe- amide-related peptides on kisspeptin activation. Intracellular calcium concentration was quantified using the calcium-sensitive dye, fura-2 acetoxymethyl ester. Gonadotropin-releasing hormone released into the medium was detected via enzyme-linked immunosorbent assay. Results showed that 100 nmol/L kisspeptin-10 significantly increased gonadotropin-releasing hormone levels (at 120 minutes of exposure) and intracellular calcium concentrations. Co-treatment of kisspeptin with 1 ?mol/L gonadotropin-inhibitory hormone or 1 ?mol/L Arg-Phe-amide-related peptide-1 significantly attenuated levels of kisspeptin-induced gonadotropin-releasing hormone but did not affect kisspeptin-induced elevations of intracellular calcium concentration. Overall, the results suggest that gonadotropin-inhibitory hormone and Arg-Phe-amide-related peptide-1 may have inhibitory effects on kisspeptin-activated gonadotropin-releasing hormone neurons independent of the calcium signaling pathway. Research Highlights (1) Kisspeptin-10 caused a significant increase in the level of gonadotropin-releasing hormone in GT1-7 cells. (2) Co-treatment of kisspeptin with gonadotropin-inhibitory hormone or Arg-Phe-amide-related peptide-1 attenuated kisspeptin-induced levels of gonadotropin-releasing hormone. (3) Arg-Phe-amide-related peptides may have inhibitory effects on kisspeptin-activated gonadotropin-releasing hormone neurons.
Keywords: Arg-Phe-amide-related peptide-1; Calcium signaling; Gonadotropin-inhibitory hormone; Gonadotropin-releasing hormone; GT1-7 cells; Hypothalamus; Kisspeptin; Neural regeneration; Neuroregeneration